Implementasi Program Cakap Digital dalam Peningkatan Literasi Digital Masyarakat - Pramono, Doni Eko Hendro; Oktaria, Intan; Purnomo, Rosyana Fitria (Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology requires society to possess adequate digital literacy and skills in order to use technology safely, ethically, and responsibly. However, various challenges are still faced by the community, including low awareness of social media ethics, personal data security, and risks in digital transactions. This community service activity aims to improve community digital literacy through the implementation of the Cakap Digital Program. The method of implementation was carried out through digital literacy socialization and educational activities using a participatory approach, including material delivery, interactive discussions, and question-and-answer sessions. The materials presented covered social media ethics, account and personal data security, safe online transactions, and an introduction to the development of artificial intelligence technology. The results of the activity indicate an improvement in participants’ understanding and awareness of the importance of using digital technology wisely and responsibly. Participants became more aware of digital risks and challenges and were able to apply digital literacy principles in their daily activities. This community service activity demonstrates that the Cakap Digital Program is effective in supporting the improvement of community digital literacy and digital competence.